2013
DOI: 10.1016/j.jaci.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Thymic stromal lymphopoietin activity is increased in nasal polyps of patients with chronic rhinosinusitis

Abstract: Background Chronic rhinosinusitis with nasal polyps (CRSwNP) is associated with Th2-dominant inflammation. Thymic stromal lymphopoietin (TSLP) is a cytokine that triggers dendritic cell-mediated Th2 inflammatory responses and that enhances IL-1-dependent Th2 cytokine production in mast cells. Although elevated levels of TSLP mRNA have been found in nasal polyps (NPs), expression of TSLP protein and its function in CRS have not been fully explored. Objectives The objective of this study was to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
180
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(200 citation statements)
references
References 35 publications
17
180
1
2
Order By: Relevance
“…This study also showed that the ILC2s from CRS patients responded to IL-33-mediated stimulation by producing IL-13 (Shaw et al 2013), further suggesting that ILC2s may contribute to the pathogenesis of allergic upper airway disease in humans. Consistent with previous findings (Mjosberg et al 2012), TSLP has recently been shown to be highly expressed in the nasal polyps of CRS patients (Nagarkar et al 2013). Although IL-33 appears to be more potent than TSLP in activating type 2 cytokine production from nasal polyp ILC2s (Mjosberg et al 2012), further studies will be required to determine which cytokines optimally promote ILC2-mediated inflammation in CRS and whether these cells have a causal role in the development of nasal polyps or pathology in CRS patients.…”
Section: Group 2 Innate Lymphoid Cellssupporting
confidence: 74%
“…This study also showed that the ILC2s from CRS patients responded to IL-33-mediated stimulation by producing IL-13 (Shaw et al 2013), further suggesting that ILC2s may contribute to the pathogenesis of allergic upper airway disease in humans. Consistent with previous findings (Mjosberg et al 2012), TSLP has recently been shown to be highly expressed in the nasal polyps of CRS patients (Nagarkar et al 2013). Although IL-33 appears to be more potent than TSLP in activating type 2 cytokine production from nasal polyp ILC2s (Mjosberg et al 2012), further studies will be required to determine which cytokines optimally promote ILC2-mediated inflammation in CRS and whether these cells have a causal role in the development of nasal polyps or pathology in CRS patients.…”
Section: Group 2 Innate Lymphoid Cellssupporting
confidence: 74%
“…TSLP expression was elevated only in eosinophilic polyps, which is consistent with previous reports investigating TSLP in polyps from patients in America (19), and it was positively correlated with levels of OX40L 1 DCs. This was not surprising because previous studies have shown that TSLP can directly induce OX40L expression on DCs (16).…”
supporting
confidence: 92%
“…538,539 The critical upstream epithelial cytokine is not completely clear, but high levels of TSLP activity have been identified in polyp homogenates. 540,541 Some evidence suggests that IL-33 may play a role as well, but these studies have yet to demonstrate increased expression of this cytokine at the protein level in NP tissue. 374,[542][543][544] In regard to IL-25, evidence in CRS is scant.…”
Section: Discussionmentioning
confidence: 99%